Investigation of Pore Structure and Water Imbibition Behavior of Weakly Cemented Silty Mudstone - Shuai Wang; Lijun Han; Qingbin Meng; Yuhao Jin; Weisheng Zhao (Advances in Civil Engineering)
Water-rock interaction of weakly cemented mudstone is intense due to its complex pore structure and mineral compositions. As primary channels for water imbibition, pore structures determine water migration. In this paper, pore properties of weakly cemented mudstone are measured by scanning electron microscopy (SEM), nitrogen adsorption/desorption (NAD), and mercury intrusion porosimetry (MIP), respectively. Water imbibition tests under free and lateral restraints are performed on self-developed water absorption instruments. The results show that skeleton aggregates, pore zone, and fissure zone constitute the basic structure of the rock, together with pore scales in nanoscale, submicron-scale, and micron-scale, respectively. The porosities of each zone are inferred with the values of 13.5%, 7.3%, and 2.3% by comparison of different methods. The main pore type is mesopore. Based on water imbibition tests, water rises along the large fissure and pore zones initially. Pores in the skeleton aggregates absorb water from pore and fissure zones subsequently. However, water imbibition is limited under lateral restraints. Owing to lateral restraints, the ascending height and rate of the sample with lateral restraints are lower than those of the sample with free confinements. The results suggest that lateral restraints can restrain water migration and water-rock interaction for weakly cemented mudstones, and measures can be taken to control swelling deformation by strengthening lateral restraints.